Digital natives and technology for L2 learning outside of the classroom - Leonor Dauzón Ledesma; Jesús Izquierdo (Universidad de Guadalajara, 2020)
Extensive research has examined the classroom-based technologies that promote L2 learning among learners, who can be considered digital migrants. This mixed-method study, however, was conducted with digital natives and examined the technologies and technological features of educational resources appealing to them, in order to practice English outside of the classroom. The quantitative data were collected through a 35-question survey administered to 158 children (aged 9-11); they were enrolled in a private school in the Southeast of Mexico. The qualitative data were collected through individual interviews from a subsample of 15 learners, who exhibited positive or negative attitudes for technology in the survey. The data analyses revealed that children felt confident using a wide variety of technologies. Nonetheless, they rarely related the use of technology for L2 learning outside of the class. They opted for technological features that fostered L2 learning in line with the cognitive processes that characterize their age.